Risk management of international expansion of Russian high-tech small and medium-sized enterprises - A. S. Prutkoy; A. V. Savin (Вестник университета, 2022)
The article discusses the specific features of the risk management of internationalisation of Russian small and medium-sized companies operating in the high-tech sector of the economy. International expansion has been considered on the example of the countries of the Visegrad Group – Poland, Czech Republic, Slovakia and Hungary. A review of the methodological base of foreign economic risk management, formed by the efforts of Russian and foreign scientists, is carried out. Possible export risks have been described and assessed on the basis of scenario modelling and factor analysis. The essence of the identified risks and the key reasons for their formation are disclosed. Methods, measures and possible actors within the risk strategy's passport to affect the identified risks, are proposed. Conclusions about the effectiveness and performance of the proposed toolkit for export risk management, are made.